(3GdJOQjH aj JeKjd GdJbQjHs - (3CHhMjGf CKjQGdOjf eMeO Hf jhSa Hf Ydj Hf MjGf GdfaRj GdZQfGWj GdfMhjs; (3GdLdOcj , YR GdOjf Ydj Hf CjOeQ Hf YeQ GdLdOcj,J (B742 (3g` s
(3ChdgG (B:s
(3hHYO, aEfj deG GNJUQJ cJGH GdebQH aj GdfMh, hMUQJ GdeYfi GdHYjO JMJ GddaX GdbQjH s
(3BNQgG (B:s
(3hLH GdMPa(B: (3YWjO aj YWhO eG djS ef daXg(B: (3MejQ aj MeGQ s
(3GdebQH dGHf YUahQ GdeJhai (B669(3g```s
(3GdfSNI egedI GdfbW CMjGfkGs
(3hHgG fXGe GdJYbjHIs
(3hCKQ WeS s
(3GfXQ GdLRA GdChd HQbe (B32 (3fMh s
(3fSNI KGfjI s
Keywords: (3GdfMhs